An interesting case of inflammatory myofibroblastic tumor presenting as cholangiocarcinoma. (2018) - Karimi, Mehrdad; Tizmaghz, Adnan; Shabestanipour, Ghazaal
Highlights: Inflammatory myofibroblastic tumor (IMT) is a reactive or inflammatory state mostly affecting the pulmonary system and commonly occurs in children and young adults. Biliary Inflammatory myofibroblastic Tumor is extremely rare. IMT should be considered by all hepatobiliary surgeons dealing with the teens with cholangiocarcinoma, to avoid unnecessary major surgical resections. Abstract: Introduction: Inflammatory myofibroblastic tumor (IMT) is a reactive or inflammatory state mostly affecting the pulmonary system and commonly occurs in children and young adults. IMT presentation in the hepatic duct bifurcation is very rare and has sporadically been reported before. Presentation of case: A 12-year-old girl presented with jaundice, pruritus which had begun 5 weeks previously. Ultrasound revealed intrahepatic biliary ductal dilation and an isoechoic 25*30 mm lesion at or near the confluence of the right and left hepatic ducts that were suggestive of a hilar cholangiocarcinoma. Limited resection was decided intraoperatively because the intraoperative frozen section assessment of the CBD, right and left hepatic duct wall samples and porta hepatis lymph nodes was normal. Histologically the tumor proved an inflammatory myofibroblastic tumor (IMT). Discussion: Almost all patients with resectable IMT should be managed with radical surgical resection or single nonsteroidal anti-inflammatory drugs. In addition, conservative treatments with NSAIDs, corticosteroids or chemotherapeutic agents could not be started in many cases due to the lack of definitive diagnosis of the mass preoperatively. Thus, surgical removal is frequently unavoidable. Conclusion: Biliary IBT is extremely rare and should be considered by all hepatobiliary surgeons dealing with the teens with cholangiocarcinoma, to avoid unnecessary major surgical resections.